Analisis Tingkat Kepuasan Pengguna Sistem Registrasi Online Seminar Widuri Computer Club Menggunakan Metode Servqual - Abriel Rizq Fauzi; Goldie Gunadi (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
This research aims to analyse the level of user satisfaction with the online registration system used by Widuri Computer Club in the seminar, by applying the SERVQUAL method. SERVQUAL is a tool used to measure service quality based on the gap between user expectations and perceptions in five main dimensions, namely reliability, responsiveness, assurance, empathy, and physical evidence. The use of an efficient online registration system is very important to ensure the convenience of participants in the registration process, therefore this research was conducted to evaluate the extent to which the existing system can meet the needs and expectations of its users. The research method used is quantitative with data collection techniques through questionnaires that are distributed to seminar participants who have used the Widuri Computer Club online registration system. The questionnaire is designed to measure user expectations and perceptions of the five dimensions of service quality. The collected data is then analysed using descriptive analysis and gap score calculation for each SERVQUAL dimension. The research results show that there is a gap between user expectations and perceptions in several dimensions, especially in the responsiveness dimension, which reflects the user's dissatisfaction with the system response time, as well as the physical evidence dimension related to the appearance and interface of the system that is considered less attractive and easy to use. Meanwhile, the dimensions of reliability and assurance obtain a relatively adequate value, although there is still room for improvement in terms of ease of access and data security. Based on these findings, it is recommended that Widuri Computer Club make improvements to the aspects that have the biggest gaps, such as speeding up response time and improving the design and functionality of the user interface. This research is expected to contribute to the development of a better online service system in the future, especially in the organisational environment based on the implementation of seminars and other events.